PENGARUH PERPUTARAN PERSEDIAAN, PIUTANG, DAN MODAL KERJA TERHADAP LABA PADA PT. PRIMA OTO MOTOR PERIODE JANUARI 2017 – DESEMBER 2021 - Yusnaldi, Yusnaldi; Pujiati, Herni (Jurnal Ilmiah Manajemen SURYA PASCA SCIENTIA, 2023)
The company leader strives to increase the value of the company and is able to manage the faktor – faktor production owned effectively and efficiently so that the company's goals are achieved. research conducted on PT. Prima Oto Motor which is a trading company that sells vehicle support which is currently a secondary need. Researchers are interested in knowing how much influence the turnover of inventory, receivables and working capital has on company profits before the pandemic and after the COVID-19 pandemic. Whether inventory turnover, receivables turnover, and working capital turnover affect profits.The research method in this study is quantitative with several tests that have been carried out descriptive analysis which states that the highest turnover occurred in January 2018, which was 0.38 and the lowest inventory turnover occurred in May 2020, which was 0.02. The heterochedasity test in this study stated that there was no heterokedasity in this study because there was no specific pattern and the point in the staterplot spread randomly. In the multicollinearity test in this study, it was stated that under the VIF value of each variable < 10 tolerance values > 0.01, then all variables did not occur multicollinearity. The autocorrelation test in this study stated that there was no autocorrelation in this study, which is known that dL < dW > dU. The multiple linear regression test in this study stated that all variables x had a positive effect on variable y. In the t test, it is known that inventory turnover and receivables turnover have an effect on profits, while working capital turnover does not affect profits. In the F test, it was found that the turnover of inventory, receivables and working capital had a simultaneous effect on the company's profit. Based on the coefficient of determination test, it is stated that variable x has an influence on variable y by 56.6%. Meanwhile, 43.4% was influenced by other variables that were not tested in the study.This shows that these components are jointly able to meet the company's needs in achieving company profits. For the management, it is expected to pay more attention and re-evaluate the turnover of inventory, receivables and working capital to be more effective and efficient so that working capital can increase company profits so as to maximize the existing potential. Key : turnover of inventory, receivables, and working capital against